Interfaces entre discurso e prática no atendimento ao adolescente autor de infração penal em Goiás: a história do Centro de Observação e Orientação Juvenil. - Teixeira, Claudia Regina de Castro (2017)
The “Center for Youth Observation and Guidance” (COOJ) was an institution designed to assist children and adolescents in situations of social vulnerability that operated in Goiânia between 1966 and 1986. In order to answer some questions concerning the proposals and practices carried out in that institution, it was established as the main objective of this research to understand the processes of emergence, development and closure of COOJ. This study was structured in a historiographical construction, which is determined by the researcher's posture, her set of values and the context in which it occurs, without necessarily intending to reach absolute truth. The process of collecting data and information occurred through the search of documents in public archives, private archives and government agencies. As a result it is possible to verify that the development of the COOJ occurred in a militaristic, hygienist and controlling scenario. The political proposal was manifested by a discourse of re-education and resocialization in accordance with the “National Policy for Child Welfare”. However, the practice proved to be very contradictory as educative action. Its deactivation in 1986 occurred concurrently to reports published by local media about the violence practiced to inmates, the bad conditions of the physical structure of the institution and the urgent need to reformulate the socio-educational assistance policy in the State. Although it is remarkable the intention of several professionals who worked in the COOJ, in the development of the proposal of reeducation and reinsertion, it is evident the distance between the discourse and the practice in the execution of the “Social Welfare and Education Policy” in the studied period.